2014
DOI: 10.1152/ajpregu.00156.2014
|View full text |Cite
|
Sign up to set email alerts
|

Effects of peripheral and spinal κ-opioid receptor stimulation on the exercise pressor reflex in decerebrate rats

Abstract: Copp SW, Stone AJ, Yamauchi K, Kaufman MP. Effects of peripheral and spinal -opioid receptor stimulation on the exercise pressor reflex in decerebrate rats. Am J Physiol Regul Integr Comp Physiol 307: R281-R289, 2014. First published June 11, 2014 doi:10.1152/ajpregu.00156.2014The exercise pressor reflex is greater in rats with ligated femoral arteries than it is in rats with freely perfused femoral arteries. The exaggerated reflex in rats with ligated arteries is attenuated by stimulation of -opioid and ␦-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…The incision was closed, and the rats were given 72 h to recover before any subsequent procedure. We did not perform any "sham" ligation procedures in this study because we have shown previously that a sham procedure does not result in an exaggerated pressor response to either static (11) or intermittent (10) hindlimb muscle contractions.…”
Section: Methodsmentioning
confidence: 99%
“…The incision was closed, and the rats were given 72 h to recover before any subsequent procedure. We did not perform any "sham" ligation procedures in this study because we have shown previously that a sham procedure does not result in an exaggerated pressor response to either static (11) or intermittent (10) hindlimb muscle contractions.…”
Section: Methodsmentioning
confidence: 99%
“…Contrary to findings concerning μ and δ receptors, stimulation of peripheral K-opioid receptors did not attenuate the exercise pressor reflex or mechanoreflex in either freely perfused or ligated rats. Stimulation of K-opioid receptors on the central endings of K-opioid receptors did, however, attenuate the exaggerated exercise pressor reflex in ligated rats (Copp et al, 2014). …”
Section: Mechanisms Contributing To Exaggerated Pressor Responsementioning
confidence: 99%
“…The DRG from freely perfused legs served as controls. We have shown recently that the pressor and cardioaccelerator responses to static contraction in sham-operated rats are not significantly different than those from rats with freely perfused sides (Copp et al 2014). Figure 9A shows the Western blots used for detecting MOR and G␣ i3 levels from four rats.…”
Section: Resultsmentioning
confidence: 97%